Studi Komparatif Aliran Besar Metode Sunnah Bil-Wus’a Ahmad Bin Hanbal Dan Metode Mashlahah Mursalah Malik Bin Anas Dalam Metodologi Studi Hukum Islam - Muhammad Yazidi Rahman (Sharia Journal and Education Center Publishing, 2024)
Islamic law has a complex and adaptive system, based on the Qur'an and Hadith as the main sources, and ijma and qiyas as complementary instruments to answer contemporary problems. In understanding and formulating Islamic law, there are two major schools of thought: the textualist school (Ahlul Hadith) and the rationalist school (Ahlur Ra'yi). The textualist school focuses on a literal understanding of the holy text, maintaining the authenticity of Islamic law as practiced during the time of the Prophet. Meanwhile, the rationalist school prioritizes reason and context in determining the law, making it more dynamic to adapt to modern challenges. The literature study research method is used to analyze the differences and similarities in the approaches of these two schools. The research was conducted by collecting relevant literature from various academic sources, analyzing the legal istinbath method applied, and identifying the strengths and challenges of each school. The results of the study show that the textualist school provides stability and loyalty to Islamic teachings, while the rationalist school offers flexibility in dealing with social change. The combination of these two approaches creates Islamic law that is strongly principled but remains relevant. This study emphasizes the importance of synergy between the textualist and rationalist approaches in answering the legal needs of Muslims in the modern era without ignoring its spiritual essence